2016
DOI: 10.1021/acs.inorgchem.6b01933
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Re6+ (5d1) Double Perovskites, Ba2MgReO6, Ba2ZnReO6, and Ba2Y2/3ReO6: Magnetism, Heat Capacity, μSR, and Neutron Scattering Studies and Comparison with Theory

Abstract: Double perovskites (DP) of the general formula BaMReO, where M = Mg, Zn, and Y, all based on Re (5d, t), were synthesized and studied using magnetization, heat capacity, muon spin relaxation, and neutron-scattering techniques. All are cubic, Fm3̅m, at ambient temperature to within the resolution of the X-ray and neutron diffraction data, although the muon data suggest the possibility of a local distortion for M = Mg. The M = Mg DP is a ferromagnet, T = 18 K, with a saturation moment ∼0.3 bohr magnetons at 3 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
(62 reference statements)
5
33
0
Order By: Relevance
“…The atomic positions in Wyckoff positions for various atoms in the stable phase are: Ba atoms are located at 8c (0.25, 0.25, 0.25), Zn positioned at 4b (0,0,0), Re sited at 4a (0.5,0.5,0.5), and O atoms at position 24e (0.25,0,0) of the unit cell. The energy variation is shown in Figure with optimized lattice constant is in close agreement with experimental and theoretical results . We have also calculated the optimized parameters analytically found similar in value with others enlisted in Table .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The atomic positions in Wyckoff positions for various atoms in the stable phase are: Ba atoms are located at 8c (0.25, 0.25, 0.25), Zn positioned at 4b (0,0,0), Re sited at 4a (0.5,0.5,0.5), and O atoms at position 24e (0.25,0,0) of the unit cell. The energy variation is shown in Figure with optimized lattice constant is in close agreement with experimental and theoretical results . We have also calculated the optimized parameters analytically found similar in value with others enlisted in Table .…”
Section: Resultssupporting
confidence: 86%
“…Further, in two calculation methods there is a negligible change in total magnetic moments where GGA + U incorporation makes exact splitting of the d ‐orbitals of Re +6 due to which a slight increase in its magnetic moment is seen. The reported values of magnetic moments show a good agreement with the experimental results having ferromagnetic character ranging from at 0 K up to 11 K …”
Section: Electronic and Magnetic Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…There are only a couple of compounds that have been reported to have J eff = 3/2 (Γ 8 ) quartet ground states thus far: Ba 2 NaOsO 6 [11][12][13], Ba 2 YMoO 6 [14], and A 2 TaCl 6 (A = Rb, and Cs) [15]. Recently, we reported that the 5d DP Ba 2 MgReO 6 [16,17] also has a spin-orbit entangle electronic state [18]. The hallmarks of the J eff = 3/2 state are the reduced effective magnetic moment and the electronic entropy of ~R ln4: when the spin and orbital degrees of freedom of the d 1 system are coupled, the spin and orbital angular momentums cancel each other, resulting in a reduced magnetic moment: the electronic entropy of ~Rln4 is clear evidence of the quartet ground sate.…”
Section: Introductionmentioning
confidence: 99%